HUBUNGAN KOORDINASI MATA DAN KAKI DAN KESEIMBANGAN DENGAN KEMAMPUAN AKURASI SHOOTING SEPAKBOLA PADA TIM NABIL FC PELALAWAN - Dama Indriyana; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the observations of the author on the Pelalawan FC player found deficiencies when shooting a lot that does not lead to the target or deviated from the goal. The instruments in this study were tests including eye and foot coordination tests using eye and foot coordination tests, balance tests using a balance test and shooting tests using an accurate shooting accuracy test. Based on the results of the study it can be concluded as follows: From the results obtained by eye and foot coordination there is a low relationship with the results of shooting in football games FC Nal Pelalawan Team, namely the acquisition of r count (0.257) 05. From results obtained by the balance there is a very low relationship with the results of shooting in the game of football Nabil FC Pelalawan namely the acquisition of r count (0.097) < from the acquisition of rabel (0.433) at α = 0.05. eye and foot balance and coordination of the results of shooting in football games Nabil FC Pelalawan namely the acquisition of Rcount (0.258) <from the acquisition of Rtabel (0.433) at α = 0.05. Key Words: Eye and Foot Coordination and Balance, Shooting Results